Micrometer Positioning Accuracy With a Planar Parallel Continuum Robot - Mauzé, Benjamin; Laurent, Guillaume J.; Dahmouche, Redwan; Clévy, Cédric (Frontiers in Robotics and AI, 2021)
Parallel Continuum Robots (PCR) have several advantages over classical articulated robots, notably a large workspace, miniaturisation capabilities and safe human-robot interactions. However, their low accuracy is still a serious drawback. Indeed, several conditions have to be met for PCR to reach a high accuracy, namely: a repeatable mechanical structure, a correct kinematic model, and a proper estimation of the model’s parameters. In this article, we propose a methodology that allows reaching a micrometer accuracy with a PCR. This approach emphasizes the importance of using a repeatable continuum mechanism, identifying the most influential parameters of an accurate kinematic model of the robot and precisely measuring them. The experimental results show that the proposed approach allows to reach an accuracy of 3.3 µm in position and 0.5 mrad in orientation over a 10 mm long circular path. These results push the current limits of PCR accuracy and make them good potential candidates for high accuracy automatic positioning tasks.